Global Spine Forum Updates: Research Supports Early Intervention - Vinall, Phil (MD Conference Express, 2015)
This article provides an introduction to AOSpine and the AOSpine Knowledge Forums including the new AOSpine thoracolumbar fracture classification system. Other topics include how the timing of surgical intervention affects safety, neurologic outcomes, and cost-effectiveness, as well as neuroprotective benefits of using the sodium channel blocker riluzole after primary spinal cord injury.